BERFIKIR SECARA TRANSPARAN DAN ARGUMENTASI (Berfungsi untuk menganalisis dan menjelaskan pentingnya berfikir secara Transparan dan logis terhadap berbagai aspek komunikasi Bisnis) - Suradi, Endang (Universitas Prof. Dr. Moestopo (Beragama), 2010)
In a typical days at work or college we are likely to be confronted with arguments coming in all shapes and sizes. - Reading the newspaper over brealifast or listening to the morning news. We will come under the influence of other persons or organisations trying to convince us of the correctness of their views on everything from the best value cereal to eat to who we should votefor in the next election.At college, we will be expected to criticallyjudge the value of what we read in books and articles, and be able to produce essays and reports which are logical and well-organised.At work, we will have reports to read (and write) in which it will be extremely important dto judge whether the conclusions and recommendations reached are correct or not.As we advance in our careers, this skill of clear thinking becomes ever more important as quick and accurate judgments have to be made on many other peoples arguments and submissions. So important is it to think clearly in relation to our own and others ideas that it is difficult to imagine a successful person who does not have this ability.The purpose of this chapter is to introduce the main types of argument used in everyday life, with a view not only to being able to convincingly demonstrate- to ourselves and our